The Influence of Salary, Family Responsibility, and Future Orientation on Financial Well-Being through Financial Mindset - Antoni, Antoni; Priyana, Yana; Supriandi, Supriandi (Westscience Press, 2025)
This study investigates the influence of salary, family responsibilities, and future orientation on the financial well-being of Generation Z, with a particular focus on the mediating role of financial mindset. Utilizing a quantitative research method, data were collected from 150 respondents through an online questionnaire using a Likert scale (1–5). Data analysis was conducted using SPSS version 25, including regression and mediation analysis. The findings reveal that salary and future orientation have a significant positive effect on financial mindset, while family responsibilities have a negative but significant effect. Furthermore, financial mindset significantly influences financial well-being and partially mediates the relationship between the independent variables and financial well-being. These results highlight the critical role of psychological factors, such as mindset, in shaping financial behavior and outcomes. The study emphasizes the need for financial education and support systems that cultivate a forward-looking and confident approach to personal finance among Generation Z.